The management of mental health in the Primary Health Care Network: An integrative review - Santos, Vitor Celestino dos; Pereira, Dyego Cruz; Bueno, Ana Luísa; Farias, Gabriel Santos; Paiva, Maykon Jhuly Martins de; Kury, Raisa Cabral; Nunes, Rodrigo Disconzi; Júnior, Tulio Cesar de Oliveira; D’Alessandro, Walmirton Bezerra; D’Alessandro, Aline Almeida Barbaresco (Seven Editora, 2024)
The management of psychotic disorders has always been an important topic of study in Medicine, and there are numerous ways to do so. Taking the perspective of Basic Health Care as a bias, these clinical conditions had their administration mechanisms modified over time. Therefore, the present research aimed to analyze the historical, epidemiological and organizational assumptions about the management of mental health cases in primary health care. From this angle, an integrative literature review on the administration of mental health in basic health care was created. That said, the descriptors “Humanization” were crossed; "Mental health"; “Primary Health Care”, in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO) and Virtual Health Library (VHL) information bases. In this way, research has highlighted numerous ways of managing psychotic disorders in Primary Health Care, highlighting the historical composition of today’s approach model, the relevance of humanization at this stage, the main conduct of Primary Care and the challenges inherent to the diagnosis of a mental disorder. Finally, it was demonstrated that there is a satisfactory interaction between the premises and precepts of Basic Health Care in the management of psychiatric disorders, which allows for care and more humanized and holistic care. DOI:https://doi.org/10.56238/sevened2024.001-035